Health risks of geogenic contaminants in gold mining areas in Geita, Tanzania - Noel Isack Kaaya; Maheswara Rao Vegi; Athanas Simon Macheyeki (Journal of Trace Elements and Minerals)
Background: Mining in Tanzania's Lake Zone, especially Geita, may release toxic elements linked to health risks like cancer, but the most hazardous PTEs and vulnerable groups are uncertain. Objectives: This study aims to assess the health risks posed by metal(loid)s in <75 µm particles of gold mine tailings for workers, children, and adults at four artisanal and small-scale gold mining (ASGM) sites in Geita: Bululu, Ifugandi, Nyarugusu, and Lwamgasa. Methods: Concentrations of metal(loid)s in tailings were measured using ICP-OES. Carcinogenic and non-carcinogenic risks were assessed for children, gold mine workers, and adult residents using the USEPA risk assessment approach. Multivariate analysis using Minitab 18 software was used for the identification of metal(loid)s source. Results: Tailings from ASGM sites contain 49 % to 54 % of particles <75 µm, which can be ingested or transported by wind, presenting significant health risks. The most carcinogenic PTEs are As (86 %), Ni (9 %), and Cr (5 %), while Cd and Pb pose negligible risks. As causes the highest risk in Bululu and Ifugandi, while Cr and Ni are most concerning in Nyarugusu and Lwamgasa. The Health Hazard Index (HI) exceeds the safe limit (1.00) in Bululu for As, while in Nyarugusu, Cr and Mn also surpass the limit. Conclusions: Geogenic contaminants from mining may cause cancer. Therefore, there is a need to mitigate pollution by using methods such as tailing stabilization, phytoremediation, better tailings management, awareness programs, health screenings, and safety regulation enforcement.